Incident cancer risk in dipeptidyl peptidase-4 inhibitor-treated patients with type 2 diabetes mellitus - Choi, Yeo Jin (Cancer Manag Res, 2019)
OBJECTIVE: It is known that patients with diabetes are susceptible to cancer development due to long-standing diabetic conditions. This study aimed to investigate new-onset cancer risk associated with dipeptidyl peptidase-4 (DPP-4) inhibitors as compared to metformin, the first-line antidiabetic agent with promising anticancer activity, in patients with type 2 diabetes mellitus (T2DM). METHODS: A retrospective cohort study of adult T2DM patients was performed at a tertiary care hospital in Korea. Patients who received comparison therapies during 2008–2017 were propensity score (PS)-matched in a 1:1 ratio either to the DPP-4 inhibitors group or to the metformin group in accordance with their primary antidiabetic therapy. RESULTS: A total of 1538 patients (769 in each group) were found eligible for study entry. Although the rate of newly diagnosed malignancy, irrespective of specific sites or types, was numerically less frequent in the DPP-4 inhibitors group, the difference in overall cancer risk between groups was not statistically significant (HR=1.00, 95% CI=0.56–1.80, P=0.998). The PS-matched patients were further stratified by relevant patient factors and diabetes severity. No signal of increased risk of malignant complications among DPP-4 inhibitor-receiving diabetic patients was detected in any of the individual strata, nor in the subgroup patients where insulin-exposed patients were excluded from study analyses in consideration of its carcinogenic properties. Patient death or incident pancreatitis events were seldom encountered in both treatment groups; hence such risks were assessed as negligible with the use of either antidiabetic therapy. CONCLUSION: This PS-matched cohort study demonstrated no elevated risk of malignant complications with DPP-4 inhibitor treatment relative to metformin treatment among T2DM patients, irrespective of patient sex, age, comorbid conditions, and diabetes severity status. Similar results were confirmed in the subgroup analyses where a potential confounding effect due to the between-group disparity in insulin co-therapy was eliminated by excluding insulin-exposed patients from risk assessments.